Presence of solar filament plasma detected in interplanetary coronal mass ejections by in situ spacecraft - Srivastava Nandita; Sharma Rahul (Journal of Space Weather and Space Climate, 2012)
Aims: To identify the solar filament plasma at 1 AU by using in situ spacecraft data. Methods: We used magnetic, plasma and compositional parameters to identify the presence of filamentary material within and outside magnetic clouds. Results: We report two cases of observed filament plasma embedded in interplanetary coronal mass ejections (ICMEs) related to a flare-associated eruptive filament and a quiescent filament eruption at different phases of solar cycle by using magnetic, plasma, and compositional parameters. Conclusions: Analysis of in situ multi-spacecraft observations of ICME structures and substructures confirms the presence of solar filament material.